The Role Of The Internet In Foreign Language Learning - Muminova Feruza Payzerakhmanovna; Nizamova Khilola Shavkatovna (Global Scientific Publishing, 2025)
This article explains the important role of the Internet in education and the significant aspects of its unlimited possibilities for the field of education. As we all know, in order to prepare the young generation that is currently growing up to perfectly learn foreign languages, to be able to communicate freely in the foreign language they are learning, there is a need to immerse themselves in the cultures of the peoples of the world through the study of foreign languages. These tasks are one of the main goals and objectives of the educational reform being implemented in our country
Keywords: Internet; globalization; websites